(untitled) (Research, Society and Development, 2021)
Objective: To gather knowledge from the literature on the importance of professional nurses in the prevention of HPV in primary care. Methodology: A descriptive, qualitative literature review was carried out using materials indexed on the LILACS, BDENF, SciELO platforms, available from the VHL - Virtual Health Library and Revista Enfermagem UERJ, after searching and applying the inclusion and exclusion criteria, a total of 16 articles were selected, published between 2011 and 2021 and written in Portuguese. Results and Discussion: The nurse has a leading role in the prevention of HPV. The deficit in health education and the failure in the management of UBSs for a holistic care of women can be cited as risk factors for HPV contamination. Thus, nursing has an important role in HPV prevention and can use health education strategies, active search and encouragement of vaccination. Conclusion: It was evident that the care of women with HPV in primary care is the consequence of an ineffective care service and a low dissemination of information, expressing failures in management, problems to establish an adequate flow of care, the need for new preventive and educational techniques, and continuing education for health professionals.